An Ovarian Pregnancy in a Patient with a History of Bilateral Salpingectomies: A Rare Case - Sadia Khandaker; Pranav Chitkara; Eric Cochran; Jed Cutler (Case Reports in Obstetrics and Gynecology)
Background. 1 in 200 ectopic pregnancies are true ovarian pregnancies that fulfill the Spiegelberg criteria. Despite being rare, multiple case reports and series have been reported. Few cases have been published in which the event was preceded by salpingectomy. Case. The patient is a 32-year-old female who presented to the emergency room with abdominal pain. She was found to be pregnant, despite a history of two previous ectopic pregnancies treated with salpingectomies. Sonography confirmed a left adnexal mass and free fluid. Surgery revealed a ruptured ovarian pregnancy which was also confirmed by pathology. Conclusion. This is a case of an ovarian pregnancy in a patient with two previous salpingectomies. It underscores the importance of searching for an ectopic pregnancy in patients with abdominal pain after fertility impairing surgery.